Institutional Factors of Micro, Mezzo and Macro Systems’ Innovative Development - SHINKEVICH, Marina V.; MISBAKHOVA, Chulpan A.; BASHKIRTSEVA, Svetlana A.; FEDOROVA, Tatyana A.; MARTYNOVA, Olga V.; BELOBORODOVA, Anastasia L. (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The relevance of the study is conditioned by the need to find the factors for stability of innovative development, the basis of which, under conditions of uncertainty of the environment, are institutions that reduce transaction costs, are responsible for the creation, diffusion and development of innovation and technology of institutionalization and management of innovative economic development. The aim of the study is to search for and organize the institutional impact factors on the innovative development and its sustainability. The article summarizes the possibilities of overcoming the limits of innovation development of the micro, mezzo and macro systems and key points of the institutional impact on innovation development, to ensure its sustainability in the environmental conditions’ uncertainty. Paper Submissions are of theoretical and practical significance for the development and implementation of federal and regional programs of competition policy and innovation development, as well as in the development of the state innovation policy strategy.